A new statistic to the theory of correlation stability testing in financial market - Shamshuritawati Sharif, 1977-; Maman Abdurachman Djauhari, supervisor; Zuhaimy Ismail, supervisor; Fakulti Sains (2013)
Thesis (Ph.D (Matematik)) - Universiti Teknologi Malaysia, 2013